FINANCIAL SLACK AND ENVIRONMENTAL PERFORMANCE ON CARBON DISCLOSURE IN INDONESIA AND MALAYSIA MINING COMPANIES - Meiliana Jaunanda; Clementinne Nathasya Putri (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
The goal of this research is to examine how environmental performance and financial slack influence carbon emission disclosure, with the solvability ratio serving as a moderator. The study uses a checklist table to assess carbon emission disclosure. The PROPER rank measures environmental performance. Financial slack is calculated by dividing cash and cash equivalents by total sales. The debt-to-equity ratio is used to determine the solvency ratio. The study used secondary data from 61 Indonesian and Malaysian mining companies listed on the Indonesia Stock Exchange and the Bursa Malaysia. The information pertains to the years 2021–2022. The sample collection approach used in the study was purposive sampling. The study's conclusions point to a clear relationship between environmental performance and carbon emission disclosure, with environmental performance positively influencing disclosure of carbon emissions. The disclosure of carbon emissions is negatively impacted by financial slack and solvency ratio. This research also shown that the solvency ratio is unable to counteract the effects of financial slack and environmental performance on disclosure of carbonemissions.